2019
DOI: 10.1177/1179573519832014
|View full text |Cite
|
Sign up to set email alerts
|

Bartonella henselae Bloodstream Infection in a Boy With Pediatric Acute-Onset Neuropsychiatric Syndrome

Abstract: Background:With the advent of more sensitive culture and molecular diagnostic testing modalities, Bartonella spp. infections have been documented in blood and/or cerebrospinal fluid specimens from patients with diverse neurological symptoms. Pediatric acute-onset neuropsychiatric syndrome (PANS) is characterized by an unusually abrupt onset of cognitive, behavioral, or neurological symptoms. Between October 2015 and January 2017, a 14-year-old boy underwent evaluation by multiple specialists for sudden-onset p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 34 publications
2
40
0
Order By: Relevance
“…36,37 In conjunction with the cases in this report, B henselae bacteremia may contribute to progressive, recalcitrant neuropsychiatric symptoms consistent with Pediatric Acute-onset Neuropsychiatric Syndrome (PANS) in a subset of patients and may be misdiagnosed as schizophrenia. 37 There is also evidence that Bartonella spp. infection may play a role in some cases of pediatric mood disorders.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…36,37 In conjunction with the cases in this report, B henselae bacteremia may contribute to progressive, recalcitrant neuropsychiatric symptoms consistent with Pediatric Acute-onset Neuropsychiatric Syndrome (PANS) in a subset of patients and may be misdiagnosed as schizophrenia. 37 There is also evidence that Bartonella spp. infection may play a role in some cases of pediatric mood disorders.…”
Section: Discussionmentioning
confidence: 57%
“…There is increasing microbiologic evidence indicating bloodstream and cerebrospinal fluid infections with one or more Bartonella spp. in patients with neuropsychiatric symptoms 36,37 . In conjunction with the cases in this report, B henselae bacteremia may contribute to progressive, recalcitrant neuropsychiatric symptoms consistent with Pediatric Acute‐onset Neuropsychiatric Syndrome (PANS) in a subset of patients and may be misdiagnosed as schizophrenia 37 .…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, these results suggest that immune activation in the brain during early-, mid-to late fetal development and adolescence to young adulthood is more likely to interfere with pathways related to synapse formation, structure and remodeling. Consistent with this speculation, accumulating evidence demonstrates that prenatal maternal infections during pregnancy 28,29 and infection events during adolescence are associated with schizophrenia 47,48 .…”
Section: Resultsmentioning
confidence: 72%
“…A recent case study suggested a candidate infectious mechanism causal agent for schizophrenia may be the bacterium responsible for cat scratch disease (i.e., "cat scratch fever") -Bartonella henselae [23]. This study linked B. henselae seropositivity and a history of cat bites and scratches to onset of schizophrenia symptoms in a 14-year-old boy.…”
Section: Discussionmentioning
confidence: 83%